Study of Ethno Cosmetics Natural Care of Batujai Village Community, West Praya, Central Lombok - Nurul Istiqomah; Nisa Isneni Hanifa; Kurniasih Sukenti (Jurnal Biologi Tropis, 2021)
Cosmetics are a major need for women everyday life, which can be seen from the increasing income of the cosmetics industry for up to 12% in 2016. Natural ingredients are the alternative to reduce the negative impact of synthetic cosmetics. Knowledge about it is obtained from generation to generation with oral traditions but has several weaknesses. The aims of study to conduct studies related to use of natural ingredients and to find out the value of the use of plants as natural care cosmetics by the people of Batujai village. This research used descriptive methods with qualitative and quantitative approaches, where quantitative data is the result of the calculation of the Index of Cultural Significance (ICS) and Fidelity Level (FL). The results showed that there were 13 natural care cosmetic ingredients consisting of 27 species and 18 families. The potions are children's rapus, rapus golam, rapus mutu, rapus wajah, soap, shampoo, mamak, kejames 1, kejames 2, kejames 3, kejames 4, serbat, and toothpaste. The highest ICS value of 42 was found in the species Oryza sativa L. and the lowest value of 6 was found in the species Amaranthus arenicola, Musa, Cocos nucifera L., Aleurites moluccanus, Aloe vera, Syzygium aromaticum (L.) Merr., Citrus aurantiifolia, Piper retrofractum Vahl, Lannea coromandelica, Jatropha curcas L., Sida rhombifolia L., Ipomoea alba L., Barringtonia racemosa, and Ipomoea sepiaria. FL values range from 25-100%.